Biochemical and molecular characteristics of Listeria monocytogenes isolates from a prosthetic mitral heart valve-bearing patient´s blood cultures - Leal, Nilma Cintra; Costa, Ana Paula Rocha da; Vilela, Marinalda Anselmo; Mendes-Marques, Carina Lucena; Almeida, Alzira Maria Paiva de (Journal of Health & Biological Sciences, 2013)
Background: In Brazil, listeriosis is not a notifiable disease; thus, the incidence of Brazilian cases remains unknown. Listeria monocytogenes is not always included in automated systems, and its detection depends on the high skill level of microbiology laboratory professionals. This paper describes the characteristics of L. monocytogenes isolates fortuitously obtained from an endocarditis case in Recife, PE, Brazil. Methods: Six bacterial isolates obtained from six blood cultures from a 28-year-old male bearing a prosthetic mitral heart valve were analyzed by PCR using primers specific of L. monocytogenes to confirm a presumptive identification, determine the serotype and presence of the virulence genes (inlA, inlB, inlC, inlJ, hly, plcA, actA, prfA) in an attempt to determine the Listeria genotype by PCR-ribotyping. Results: The samples were identified as L. monocytogenes 4b. All investigated virulence genes were amplified by PCR, and the identity of the amplified segments was confirmed by sequencing. A deletion of 105 base pairs was detected in the actA gene. All of the samples generated the same PCR-ribotype pattern, clustered into a single ribotype, and were considered a single strain. Conclusion: L. monocytogenes infection should be considered in endocarditis differential diagnoses, especially among high-risk groups, due to its high pathogenicity and the environmental ubiquity.